Bioeconomy and Circular Economy in the European Food Retail Sector - Istudor, Laura-Gabriela; Suciu, Marta-Christina (European Journal of Sustainable Development, 2020)
The paper highlights the importance of analysing corporations’ activities and their policies addressing non-financial indicators, in line with the current global concerns regarding sustainability and bioeconomy. It aims at contributing to a better understanding of the concepts of circular economy and bioeconomy, while analysing corporations’ behaviours regarding these topics. As Corporate Social Responsibility (CSR) standards have become frameworks for illustrating socially and environmentally responsible behaviours, the number of companies that adopt such standards for the elaboration of sustainability reports has increased. Since the publication of sustainability reports became mandatory as of 2018, we consider that their documentation is in an incipient phase. This paper uses an empirical content-based analysis of sustainability reports released by corporations in the food retail sector inside the European Union. The selected retailers report non-financial performance following the guidelines of international social responsibility codes elaborated by the non-profit organization Global Reporting Initiative (GRI). The results of the analysis show different levels of involvement in sustainable practices across the corporations considered. Furthermore, the paper provides the main challenges regarding the implementation of sustainable methods of doing business, as well as the main impacts of adopting CSR standards for the supply chain. Keywords: Bioeconomy, circular economy, sustainability, CSR, corporations